The role of grain boundary microchemistry in irradiation-assisted stress corrosion cracking of a Fe-13Cr-15Ni alloy. (1st October 2017) - He, Mo-Rigen; Johnson, Drew C.; Was, Gary S.; Robertson, Ian M.
Abstract: A novel explanation based on the variation of grain boundary composition is proposed to elucidate the localized nature of irradiation-assisted stress corrosion cracking, i.e., intergranular cracking is observed only at specific sites of random high-angle grain boundaries, in a Fe-13Cr-15Ni austenitic model alloy subjected to proton irradiation and straining in a high-temperature water environment. Specifically, this work presents electron microscopy characterization of multiple cracked and un-cracked grain boundary sites and the neighboring oxides. The depletion of Cr and enrichment of Ni, as expected due to radiation-induced segregation, is observed at grain boundaries far from the crack tip (for cracked sites) or the metal surface (for un-cracked sites), and such modification of grain boundary composition is enhanced in the vicinity of the corrosion reaction front. Unexpectedly, grain boundary sites beyond the crack tip always present a lower Ni content and higher Cr content than the un-cracked sites on the same grain boundary. Overall, it is proposed that the site-specific susceptibility to stress corrosion cracking is governed by the grain boundary microchemistry, which determines not only the quantity of Cr, but also the efficiency of Cr transport to the reaction front and thus the protectiveness of the inner oxide. These effects of local composition may be further coupled with the local structure of and the local stresses interacting with the random high-angle grain boundaries. Graphical abstract: Image